2008
DOI: 10.1074/jbc.m804086200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Blocking Effects of the Acetaldehyde-derived DNA Lesion N2-Ethyl-2′-deoxyguanosine on Transcription by Multisubunit and Single Subunit RNA Polymerases

Abstract: Acetaldehyde, the first metabolite of ethanol, reacts with DNA to form adducts, including N 2 -ethyl-2-deoxyguanosine (N 2 -Et-dG). Although the effects of N 2 -Et-dG on DNA polymerases have been well studied, nothing is known about possible effects of this lesion on transcription by RNA polymerases (RNAPs). Using primer extension assays in vitro, we found that a single N 2 -Et-dG lesion is a strong block to both mammalian RNAPII and two other multisubunit RNAPs, (yeast RNAPII and Escherichia coli RNAP), as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
5
18
0
Order By: Relevance
“…Owing to the lack of effect of N 2 - dG lesions on DNA replication, this type of lesions have been suggested to be “stealth lesions” 46 . The results from the present study, along with previous in vitro studies 46,47 , showed that these minor-groove N 2 - dG lesions are able to strongly inhibit DNA transcription when present on the DNA template strand. N 2 -ethyl-2′-deoxyguanosine ( N 2 -EtdG) was found, from primer extension assays, to be a strong block to both single-subunit T7 RNAP and multi-subunit RNAPs in vitro 47 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Owing to the lack of effect of N 2 - dG lesions on DNA replication, this type of lesions have been suggested to be “stealth lesions” 46 . The results from the present study, along with previous in vitro studies 46,47 , showed that these minor-groove N 2 - dG lesions are able to strongly inhibit DNA transcription when present on the DNA template strand. N 2 -ethyl-2′-deoxyguanosine ( N 2 -EtdG) was found, from primer extension assays, to be a strong block to both single-subunit T7 RNAP and multi-subunit RNAPs in vitro 47 .…”
Section: Discussionsupporting
confidence: 81%
“…The results from the present study, along with previous in vitro studies 46,47 , showed that these minor-groove N 2 - dG lesions are able to strongly inhibit DNA transcription when present on the DNA template strand. N 2 -ethyl-2′-deoxyguanosine ( N 2 -EtdG) was found, from primer extension assays, to be a strong block to both single-subunit T7 RNAP and multi-subunit RNAPs in vitro 47 . In addition, mammalian RNAPII was found to exclusively incorporate the correct nucleotide opposite N 2 -EtdG 47 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Formaldehyde, an environmental concern, reacts with the exocyclic amino group of deoxyguanosine (G), to produce N 2 -methylG [16]. Ethanol is enzymatically oxidized to acetaldehyde, which forms N 2 -ethylG, which has been observed in liver DNA and urine of alcoholic patients [17]. With both of these reactions [13, 14], 2-electron reduction of the intermediate imine is required to balance the stoichiometry.…”
Section: Environmental Mutagens Cause Dna Damagementioning
confidence: 99%
“…RNAPII is generally blocked by more bulky base lesions, e.g. , N 2 -ethyldeoxyguanosine, although the RNA polymerase can insert a C opposite such modifications in some instances [55]. Interference of RNA polymerase progression during transcription has been shown to activate certain cell death responses, and may be particularly relevant to non-dividing cell populations, such as neurons, and thus in diseases of the brain [56].…”
Section: Dna and Rna Polymerase Action At Oxidatively Generated Lesionsmentioning
confidence: 99%